How to get your biomedical paper published : a practical guide for graduate students and postdocs - Boelsterli, Urs A 1948- ([Lugar de publicación no identificado] : Karger, 2020)
This book is a modern, practical guide that will help you transform your important research data into a scientific paper that can be submitted for publication to a peer-reviewed international journal. It explains the process of designing each section of a research paper and assembling its parts into a coherent and logical 'story' that will be read and understood, remembered, and cited. The book is a must-have for international graduate students and postdocs who feel the need to publish their data in our tough and highly competitive research environment. With its many timely links to online resources, this guide will not only help you improve and optimize your paper writing skills but also show you how to get your biomedical paper published successfully.
Keywords: MEDICINA -- ARTE DE ESCRIBIR; ESCRITOS ACADEMICOS; INFORMES DE INVESTIGACIÓN